Best candidate routing algorithms integrated with minimum processing time and low blocking probability for modern parallel computing systems - Aadel M. Alatwi; Ahmed Nabih Zaki Rashed; Ahmed M. El-Eraki; Iraj Sadegh Amiri (Institute of Advanced Engineering and Science, 2020)
This study has clarified the best candidate routing algorithms integrated with minimum processing times and low blocking probabilities for modern parallel computing systems. Different methods were employed, such as the fast window method (FWM), fast bitwise window method (FBWM), and fast improved window method (FIWM), to upgrade the processing time and reduce the network delay time. In addition, different algorithms were studied such as the fast window ascending, the fast window descending, the fast window sequential algorithm, and the fast window sequential down algorithms; these were studied to show the numerical results of the networks’ blocking probabilities, processing times, and delay times.